Permeability of aggregates/ Mohamad Zaidi Ibrahim - Ibrahim, Mohamad Zaidi (1997)
In civil engineering projects mere is a lot situation that involves with permeability of soils. For example, water seepage through the earth dam, drainage blankets beneath the road embankments and road subbase. The problem mat associated with the seepage through highway base and subbase can cause major failure. Thus, it is important to understand the permeability characteristics of aggregates km highway base and subbase.